Overexpression and purification of Treponema pallidum rubredoxin; kinetic evidence for a superoxide-mediated electron transfer with the superoxide reductase neelaredoxin - Auchère, Françoise (2013)
J Biol Inorg Chem (2004) 9: 839–849 DOI 10.1007/s00775-004-0584-6